Imagery and discursive deconstruction: what do the didactic books of history on the Indians indicate in Brazil? / Desconstrução imagética e discursiva: o que aponta os livros didáticos de história sobre os índios? - Maria Aparecida Vieira de Melo (Universidade Estadual de Alagoas, 2017)
This paper presents an analysis of the images represented in textbooks about the Indians. This is on the assumption that sociodiversidades are still taken on a mythical perspective. Hence it is important to understand how they are being depicted Indians in textbooks? This discussion is based light of authors, as SILVA (2009); SILVA (2015); SANTOS AND CHAUI (2002); MARTINS (2009); COELHO (2016) and BRAZIL (2012, 1996, 2008). It aims to analyze the images and speeches steeped in history textbooks on the Indians, and more specifically identify the social representations of the Indians, observe and demystify some images and speeches still the reductionist paradigm about indigenous peoples. Methodologically, this work was developed through brainstorming (MOURA E RIBEIRO, 2015), the ideas set out the following guiding problematizations: As we look at the current textbooks regarding the approach to indigenous issues? What advances and continuities identified? What we consider more lacunar and most significant in the analyzed books? After the analysis of these issues was possible to reach the conclusion that indigenous sociodiversidades should produce educational materials about themselves, to demystify the folkloric, mythological and stereotypical view that is still in the national program of textbooks (PNLD) in full contemporaneity